Altered Fecal Metabolites and Colonic Glycerophospholipids Were Associated With Abnormal Composition of Gut Microbiota in a Depression Model of Mice - Gong, Xue; Huang, Cheng; Yang, Xun; Chen, Jianjun; Pu, Juncai; He, Yong; Xie, Peng (Frontiers in Neuroscience, 2021)
The microbiota-gut-brain axis has been considered to play an important role in the development of depression, but the underlying mechanism remains unclear. Gastrointestinal tract is home to trillions of microbiota and colon is considered as an important site for the interaction between microbiota and host, but few studies have been conducted to evaluate the alterations in colon. Accordingly, in the study, we established a chronic social defeated stress (CSDS) mice model of depression. We applied 16S rRNA gene sequencing to assess the gut microbial composition, gas and liquid chromatography mass spectroscopy to identify fecal metabolites and colonic lipids, respectively. Meanwhile, we used spearman’s correlation analysis method to evaluate the associations between the gut microbiota, fecal metabolites, colonic lipids and behavioral index. In total, there were 20 bacterial taxa and 18 bacterial taxa significantly increased and decreased, respectively, in the CSDS mice. Furtherly, microbial functional prediction demonstrated disturbance of lipid, carbohydrate and amino acid metabolism in the CSDS mice. We also found 20 differential fecal metabolites and 36 differential colonic lipids (in the category of glycerolipids, glycerophospholipids and sphingolipids) in the CSDS mice. Moreover, correlation analysis showed fecal metabolomic signature was associated with the alterations in the gut microbiota composition and colonic lipidomic profile. Of note, three lipids (PC(16:0/20:4), PG(22:6/22:6) and PI(18:0/20:3), all in the category of glycerophospholipids) were significantly associated with anxiety- and depression-like phenotypes in mice. Taken together, our results indicated the gut microbiota might be involved in the pathogenesis of depression via influencing fecal metabolites and colonic glycerophospholipid metabolism.